IMPACT OF THE COVID-19 PANDEMIC ON PUBLIC POLICY IN THE LOCAL HEALTH SECTOR A MULTI-LEVEL ANALYSIS - Aroni, Defri; Sulistiyowati, Anisa Nanang; Popang, Christina Tien; Kusuma, Ardhanari Hendra; Alhamda, Syukra (Alqaprint Jatinangor, 2023)
This study presents a comprehensive multi-level analysis of the impact of the COVID-19 pandemic on public policy in the local health sector. Through an examination of policy changes, resource allocation, and response strategies across various local government levels, the research aims to understand the dynamic interplay between the pandemic and health policy adaptations. Utilizing a mixed-methods approach, the study combines quantitative data from policy documents and healthcare statistics with qualitative insights from interviews with healthcare professionals and policymakers. The findings reveal significant shifts in public health policy, emphasizing a rapid transition towards telehealth, increased focus on mental health services, and restructured emergency response protocols. The study also highlights the challenges faced by local health sectors, including resource constraints and the need for effective communication strategies. These adaptations and challenges underscore the critical role of local governance in responding to global health crises and the necessity for flexible, resilient health systems. The study contributes to the understanding of pandemic response mechanisms at the local level and offers insights into policy formulation and implementation in the face of public health emergencies.